Quinoa Ameliorates Hepatic Steatosis, Oxidative Stress, Inflammation and Regulates the Gut Microbiota in Nonalcoholic Fatty Liver Disease Rats - Lingyue Zhong; Wei Lyu; Zihan Lin; Jun Lu; Yanlou Geng; Lihua Song; Heng Zhang (Foods, 2023)
A long-term high-fat diet causes hepatic steatosis, which further leads to oxidative stress and inflammation. In this study, we firstly investigated the regulation effects of different amounts of quinoa on hepatic steatosis, oxidative stress, and inflammation of rats fed a high-fat diet, then the gut microbiota was dynamically determined. Sprague–Dawley (SD, male) rats were randomized into four groups: normal controls (NC, fed standard chow), model groups (HF, fed a high-fat diet), low quinoa intake (HF + LQ), and high quinoa intake (HF + HQ) groups, which were supplemented with 9% and 27% quinoa in the high-fat feed (equivalent to 100 g/day and 300 g/day human intake, respectively). The results showed that quinoa intake significantly inhibited the hepatomegaly and splenomegaly, ameliorated hepatic steatosis pathologically; effectively rescued the decrease in the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) and the increase in malondialdehyde (MDA). The levels of tumor necrosis factor-α (TNF-α), interleukin-10 (IL-10), transforming growth factor-β (TGF-β), and leptin in rats of two quinoa groups were close to those of the NC group. Besides, high quinoa intake significantly increased the relative abundance of Akkermansia, and low quinoa intake significantly increased the relative abundance of Blautia at the genus level. The relative abundances of Blautia and Dorea in rats in the HF + HQ group were lower than those in rats in the HF + LQ group. In addition, the relative abundances of Clostridium and Turicibacter of rats in the two quinoa intervention groups were lower than those of rats in the HF group after 12 weeks of intervention. In summary, quinoa exhibits a series of beneficial effects in the prevention of nonalcoholic fatty liver disease (NAFLD) and is suggested to be a component of a daily diet for the prevention of NAFLD.